The role of platelet-derived ADP and ATP in promoting pancreatic cancer cell survival and gemcitabine resistance - Elaskalani, Omar; Falasca, Marco; Moran, N.; Berndt, Michael; Metharom, Pat (MDPI AG, 2017)
Platelets have been demonstrated to be vital in cancer epithelial-mesenchymal transition (EMT), an important step in metastasis. Markers of EMT are associated with chemotherapy resistance. However, the association between the development of chemoresistance, EMT, and the contribution of platelets to the process, is still unclear. Here we report that platelets regulate the expression of (1) human equilibrative nucleoside transporter 1 (hENT1) and (2) cytidine deaminase (CDD), markers of gemcitabine resistance in pancreatic cancer. Human ENT1 (hENT1) is known to enable cellular uptake of gemcitabine while CDD deactivates gemcitabine. Knockdown experiments demonstrate that Slug, a mesenchymal transcriptional factor known to be upregulated during EMT, regulates the expression of hENT1 and CDD. Furthermore, we demonstrate that platelet-derived ADP and ATP regulate Slug and CDD expression in pancreatic cancer cells. Finally, we demonstrate that pancreatic cancer cells express the purinergic receptor P2Y 12 , an ADP receptor found mainly on platelets. Thus ticagrelor, a P2Y 12 inhibitor, was used to examine the potential therapeutic effect of an ADP receptor antagonist on cancer cells. Our data indicate that ticagrelor negated the survival signals initiated in cancer cells by platelet-derived ADP and ATP. In conclusion, our results demonstrate a novel role of platelets in modulating chemoresistance in pancreatic cancer. Moreover, we propose ADP/ATP receptors as additional potential drug targets for treatment of pancreatic cancer. © 2017 by the authors.